Neuroimaging features of Amyotrophic Lateral Sclerosis - Chipika, Rangariroyashe Hannah (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2024)
Novelty: Because the vast majority of ALS imaging studies focus on evaluating motor pathology, the focus and novelty of this work is the nuanced characterisation of extra-motor involvement in a genetically stratified cohort of ALS patients. Sensory, infratentorial and subcortical structures were assessed comprehensively in multimodal analyses. The thalamus and amygdala were segmented into their individual nuclei to examine their volumetric profile, as the involvement of these nuclei has not been comprehensively characterised to date in ALS. The significance of extra-motor involvement in ALS is that subcortical and frontotemporal disease burden may contribute to neuropsychological deficits with implications for multidisciplinary management, clinical trial participation, caregiver burden, adherence to therapy and compliance with supportive interventions. Cerebellar pathology in ALS has also been prooly characterised to date despite its contribution to speech, swallowing, gait and cognitive difficulties. Rationale: The core neuroimaging signature of ALS includes motor cortex, brainstem, corticospinal tract, and spinal cord degeneration. It is increasingly recognised as a multi-system disorder and extra-motor involvement is observed to be part of the disease process. Sensory dysfunction is relatively under evaluated. There is a prevailing notion that sensory pathways may be relatively spared in ALS despite evidence of sensory disturbance that has been observed in ALS patients clinically, in electrophysiology, neuroimaging and neuropathology for several decades. We hypothesised that cerebral structures involved in somatosensory processes are not spared in ALS and sought to evaluate cerebral structures involved in sensory processes. While ALS is primarily characterized by the degeneration of upper and lower motor neurons, it is now recognized as a multi-system disorder. Cerebellar pathology in ALS has been demonstrated by a multitude of neuroimaging and neuropathology studies, however, anatomical patterns of cerebellar disease-burden are poorly characterised in vivo, cerebro-cerebellar connectivity changes are mostly inferred from functional studies, and the cerebellar signatures of specific genotypes are not firmly established. Based on these considerations, our main hypothesis is that focal cerebellar pathology may be detected instead of global cerebellar degeneration with the selective vulnerability of specific cerebellar lobules. Additionally, we hypothesised that focal intra-cerebellar pathology is accompanied by selective cerebro-cerebellar disconnection. Our objective was the systematic evaluation of cerebellar grey and white matter alterations, cerebellar peduncle integrity and cerebro-cerebellar connectivity in ALS. Subcortical grey matter degeneration has been consistently observed both post mortem and in vivo. Thalamus pathology in ALS has been evaluated by dedicated structural, metabolic, and functional imaging studies. The thalamus however is typically evaluated as a single structure in ALS. Overall thalamic atrophy has been identified by both neuroimaging and post mortem histopathology studies in ALS, but the involvement of specific nuclei has not been comprehensively characterised to date. Based on the review of the literature, we hypothesised, that the "global" thalamus pathology reported by previous imaging studies in ALS is driven by focal changes in susceptible nuclei. Building on accruing evidence of overall thalamic involvement in ALS, the main objective was the characterisation of regional thalamic pathology in sporadic, C9orf72 negative ALS at a nuclear level. An additional objective was to evaluate if PLS and C9orf72 positive ALS patients have distinctive thalamic signatures. Dedicated amygdala studies are not only sparse in the ALS imaging literature but their findings are strikingly inconsistent. Some of the inconsistency may be explained by differences in imaging methodology and patient selection, but the most likely cause of the inconsistency is that the amygdala is typically evaluated as a single structure in ALS. The involvement of specific nuclei has not been systematically evaluated to date. Based on the available histopathology literature we hypothesised that selective nuclear degeneration may be captured in the amygdala of ALS patients using high-resolution structural imaging, in-depth genetic and clinical profiling and conservative structural analysis pipelines. Based on the clinical phenotype of GGGGCC hexanucleotide repeat expansion carriers in C9orf72 we additionally hypothesised that genotype-specific amygdalar signatures may be captured. Accordingly, our objective was the systematic evaluation of amygdala pathology in vivo in a large cohort of genetically and phenotypically characterised motor neuron disease patients using both measures of the entire amygdala and evaluating alterations in specific nuclei. Main objectives: The main objectives of this thesis were: 1. To perform a systematic review of existing presymptomatic and symptomatic studies in ALS to identify common themes, stereotyped shortcomings, and key learning points for future studies. 2. To perform a systematic review of existing neuroimaging, electrophysiological, biopsy, post-mortem and animal studies that report sensory deficits in ALS and other motor neuron diseases to identify evidence of sensory involvement. 3. To systematically evaluate cerebral grey and white matter structures involved in the processing, relaying and mediation of sensory information. 4. To review in vivo and post mortem evidence for cerebellar degeneration in ALS. 5. To perform a comprehensive and multiparametric evaluation of both intra-cerebellar pathology and cerebro-cerebellar connectivity in a genetically stratified cohort of patients with ALS. 6. Individually evaluate nuclei of the thalamus to identify genotype and phenotype-specific focal thalamic involvement in C9+ ALS, C9- ALS and PLS patients in comparison to healthy controls. 7. Individually evaluate nuclei of the amygdala to comprehensively characterise amygdala pathology in C9+ ALS, C9- ALS and PLS patients in comparison to healthy controls. Clinical relevance: The degeneration of somatosensory, auditory and visual pathways was observed. This may have important clinical ramifications which are easily overlooked in the context of predominant pyramidal and LMN degeneration. Subtle sensory dysfunction, such as proprioceptive deficits, may exacerbate mobility, contribute to fall risk, impair dexterity, and worsen bulbar dysfunction, therefore comprehensive sensory testing should be considered as part of the multidisciplinary assessments. Selective, genotype-associated patterns of cerebellar degeneration were observed. Pathognomonic ALS symptoms which are typically attributed to other anatomical regions, such as dysarthria, dysphagia, pseudobulbar affect, eye movement abnormalities and cognitive deficits may be modulated, exacerbated or partially driven by cerebellar changes in ALS. The thalamus is implicated in both motor and cognitive dysfunction, as degeneration of the motor and sensory nuclei of the thalamus as well as nuclei which mediate memory and executive functions was observed. Pathology in the amygdala which plays a role in a variety of sensory, cognitive and emotional was also demonstrated. Multi-parametric neuroimaging has the potential to facilitate the monitoring of disease progression by tracking changes in selected regions of interest over time and to facilitate the classification of heterogeneous cohorts which will enable meaningful interpretation of individual scans in diagnostic, monitoring and prognostic applications.
APPROVED
Keywords: amyotrophic lateral sclerosis; motor neurone disease; neuroimaging; magnetic resonance imaging